Theoretical approach to the cephalometric diagnosis of third molar eruption - Mercedes Rodríguez del Toro; Liuba González Espangler; Cecilia Venzant Fontaine (Centro Provincial de Información de Ciencias Médicas, 2022)
The cephalometric diagnosis of third molars, as the molar group that heads the list of dental retentions, has been very variable and controversial from the clinical to the most modern radiographic methods. A literature review was carried out from January 2017 to March 2020; consulting articles, theses and texts available in databases; enlisting a total of 33 bibliographical references from which 27 were selected. The selection criteria were the direct relation with the subject, updating level in the last 5 years, as well as their methodological quality. The objective was aimed at describing the theoretical approaches to cephalometric diagnosis of third molar eruption. The review showed that there is a wide variety of studies on  cephalometric diagnosis of third molar eruption with different limitations, each one contributing with their own approach to the subject, with isolated aspects on the etiology of the abnormal eruption in foreign contexts, offering measures that do not adjust to the Cuban population, representing 72.2 % in the last 5 years, including texts, not so updated, but which were of essential consultation due to the importance of their contents. It was concluded that the theoretical approaches presented by the literature on cephalometric diagnosis of third molar eruption are distinguished by the use of different foreign methods in diverse populations; highlighting a Cuban method applicable to the local and national context.